Periodontal Pathogens and Their Association with Cardiovascular Diseases: Patogen Periodontal dan Hubungannya dengan Penyakit Kardiovaskular - Hussam Hashim Mohammed; Zina Lafta Hassan; Zahraa Khudhair Dawood; Osama A. Mohsein (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Cardiovascular diseases (CVDs) remain the leading global cause of mortality, and recent evidence suggests a bidirectional relationship between systemic inflammation and periodontal disease (PD). Specific Background: Oral microbiota dysbiosis, particularly involving pathogens such as P. gingivalis, A. actinomycetemcomitans, and T. forsythia, has been implicated in CVD progression through inflammatory and metabolic pathways. Knowledge Gap: While previous studies have highlighted possible associations, limited data exist regarding the prevalence of these pathogens and their correlation with systemic inflammatory markers and cardiovascular risk factors in Middle Eastern populations. Aim: This study investigated the prevalence of key periodontal pathogens in patients with CVD and their relationship with systemic biomarkers and cardiovascular risk indicators. Results: A total of 150 CVD patients and 50 healthy controls were analyzed. Patients exhibited significantly higher prevalence of periodontal pathogens (74% P. gingivalis, 56% A. actinomycetemcomitans, 62% T. forsythia), elevated inflammatory markers (CRP, IL-6, TNF-α), dyslipidemia, and increased BMI compared with controls (p < 0.001). Pathogen prevalence correlated positively with CVD severity. Novelty: This study provides region-specific evidence linking periodontal pathogens to systemic inflammation and cardiovascular risk. Implications: The findings underscore the importance of integrating oral health care into cardiovascular disease prevention and management strategies.Highlight : Periodontal pathogens are found more frequently in patients with CVD. Increased inflammatory markers are associated with disease severity. Risk factors such as high cholesterol increase the likelihood of CVD. Keywords : Cardiovascular Disease, Periodontal Pathogens, P. Gingivalis, CVD Risk Factors, Inflammatory Markers